Researching A New Regenerator Device - Obidov Avazbek Azamatovich, Mamadjanov Shavkatjon Olimzhanovich (Scientific Trends, 2023)
In this article, research has been carried out to improve the RX regenerator used in the cleaning processes of cotton gins. The effect of changing the parameters of the drum with rubber slats, proposed in the study, on the efficiency of cotton regeneration has been studied and the maximum level of efficiency has been determined.
Keywords: Regenerator, cotton, weeds, rubber-slatted drum, cotton particle, brush drum, regeneration effect, enterprise, slats, parameter, working body, grate.